Carbon dioxide as chemical feedstock - Aresta, Michele, 1940- (Wiley-VCH ; John Wiley [distributor], 2010)
Filling the need for an up-to-date handbook, this ready reference closely investigates the use of CO2 for ureas, enzymes, carbamates, and isocyanates, as well as its use as a solvent, in electrochemistry, biomass utilization and much more. Edited by an internationally renowned and experienced researcher, this is a comprehensive source for every synthetic chemist in academia and industry.